Origami animal sculpture : paper folding inspired by nature - Szinger, John. (Tokyo : Tuttle Pub., 2014)
"Origami artist John Szinger shares his unique vision of the wild with how-to-fold instructions for 22 intermediate-to-advanced models"--Provided by publisher.
Asian elephant -- Adirondack camp -- Canoe -- Lean-to -- Adirondack chair -- Adirondack animals -- Common loon -- Foxy fox -- Brown bear -- Adirondack moose -- Insects -- Inchworm -- Butterfly -- Cephalopods -- Octopus -- Cuttlefish -- Giant squid -- Arctic marine mammals -- Bull walrus -- Elephant seal -- Narwhal -- Hex base critters -- Lizard -- Snapping turtle -- Frog -- Five-banded armadillo -- American turkey -- Fivefold rose.
Adult.
Adult
DVD.
Keywords: CRAFTS & HOBBIES / Origami; CRAFTS & HOBBIES / Papercrafts; Origami; Paper animal making; Paper crafts